Survival of Pediatric Leukemia: The Role of Social Determinants - Palvasha, Qureshi; Muna, Abdalla; Tasnim, Abdalla; Sahar, Amedi (Université d'Ottawa | University of Ottawa, 2017)
In most high-income countries, leukemia is the most common cancer in children. Currently, overall survival (OS) of children with acute leukemia is 90% in gratitude to advances in research and therapy. The goal of this structured review is to identify the association between ethnicity, social environment and survival-related outcomes of cancer treatments among children with leukemia. A search strategy was developed and applied in PubMed, EMBASE, ProQuest and Ovid (Medline) using relevant key terms related to survival related and socioeconomic factors. Electronic searches from inception to November 15th, 2017 were performed. Of the 175 publications screened for eligibility, 30 studies met the criteria for full review, and 9 studies met final inclusion criteria. The overall 5-year survival rates being reported in the studies ranged from 69.5% to 92%, with lower survival percentages coming from studies that indicate involvement of socio-demographic factors such as race and poverty. Other studies suggested no association between the survival rates as well as mortality rates and socio-demographic factors. Various studies have provided evidence and indicated that children with leukemia belonging to specific ethnic groups, and economic minority groups experience inferior survival outcomes as compared to their advantaged majority counterparts.